Comparison of two dimensional quantitative coronary angiography (2D-QCA) with optical coherence tomography (OCT) in the assessment of coronary artery lesion dimensions. (1st June 2015) - Mazhar, J.; Shaw, E.; Allahwala, U.K.; Figtree, G.A.; Bhindi, R.
Abstract: Objectives: There is limited data on how well 2D-QCA and OCT agree with each other for measurement of coronary artery lumen dimensions. We aimed to assess the agreement between the two modalities. Methods: Patients undergoing OCT for assessment of coronary artery lesions were reviewed. Minimum luminal diameter (MLD), proximal reference diameter and distal reference diameter were measured for each lesion prior to stenting. Results: OCT was performed in 64 patients and 40 lesions were suitable for analysis. There was a good correlation for proximal and distal reference diameters (r = 0.86, p < 0.0001 and r = 0.92, p < 0.0001 respectively). There was good agreement on Bland–Altman analysis; the proximal and distal reference diameters measured by QCA were on average 0.09 mm (95% CI, − 0.52 to 0.53 mm) and 0.1 mm (95% CI, − 0.59 to 0.6 mm) smaller than OCT respectively. There was a satisfactory correlation (r = 0.63, p = < 0.0001) between QCA and OCT for MLD. However, the MLD by QCA was 0.49 mm (95% CI, − 1.57 to 0.59 mm) smaller than OCT, suggesting a poor agreement for MLD. Conclusions: There is a good correlation and agreement between QCA and OCT for measurement of proximal and distal reference diameters. However, the MLD was underestimated by QCA.